Species composition and fire: non-additive mixture effects on ground fuel flammability - Van Altena, Cassandra; van Logtestijn, Richard; Cornwell, William; Cornelissen, Hans (Frontiers in Plant Science, 2012)
Biodiversity effects on many aspects of ecosystem function have been well documented. However, fire is an exception: fire experiments have mainly included single species, bulk litter, or vegetation, and, as such, the role of biodiversity as a determinant of flammability, a crucial aspect of ecosystem function, is poorly understood. This study is the first to experimentally test whether flammability characteristics of two-species mixtures are non-additive, i.e. differ from expected flammability based on the component species in monoculture. In standardized fire experiments on ground fuels, including monocultures and mixtures of five contrasting subarctic plant fuel types in a controlled laboratory environment, we measured flame speed, flame duration and maximum temperature. Broadly half of the mixture combinations showed non-additive effects for these flammability indicators; these were mainly enhanced dominance effects, where the fuel types with the more flammable value for a characteristic determined the flammability of the whole mixture. The high incidence of species non-additive effects on ground fuel flammability suggest that the combinations of fuel types may have important effects on ground fire regimes in vegetations differing or changing in species composition.